E-075 Impact of coagulation disorders on short-term in-hospital outcomes in patients undergoing spinal fusion procedures. (22nd July 2019) - Colburn, T; Tong, K; Wang-Selfridge, A; Wright, B
Abstract : Background: Spinal fusion is a surgical procedure utilized to treat or alleviate several spinal diagnoses including: tumor, spinal stenosis, degenerative disc disease, scoliosis, and spondylolisthesis. Previous studies have explored clinical outcomes for this intervention. This study aims to further investigate short-term outcomes of patients after spinal fusion by looking at the impact of coagulation disorders. Methods: This retrospective cohort study utilized data from the Nationwide Inpatient Sample (NIS) to identify adult patients (18+) from 2012–2015 who underwent spinal fusion. ICD-9 codes identified these patients; specifically patients diagnosed with a coagulation disorder. Any patients missing important clinical identifiers (age, gender, cause of death) and patients without spinal fusion intervention were excluded. Data analyses assessed hospital length of stay (LOS), inpatient charges, average age of admission and mortality rate. Results: Of the 290, 752 patients that underwent spinal fusion procedure, 182 had the diagnosis of a coagulation disorder (CD): Mean mortality rate of patients was significantly increased (4.9%, CD vs. 0.6% no CD, p = 0.0001) LOS in patients with CD who underwent spinal fusion was significantly increased (12.87 days, CD vs. 4.02 days, no CD, p = 0.0001) Total hospital charges were significantly increased ($289, 377.06, CD vs. 98, 232.87, no CD, p = 0.0001) Mean age of patients at admission was significantly increased (60.68 years, CD vs. 57.69 years, no CD, p = 0.008) Conclusion: Patients with coagulation disorders who undergo a spinal fusion procedure suffer from increased mortality rate, LOS, total hospital charges, and age at admission. This study aims to provide physicians with information in the management of patients with coagulation disorders that undergo spinal fusion procedures. Peri-procedural patient optimization could provide a potential avenue to lower LOS, total in-hospital charges, and mortality in patients. Disclosures: T. Colburn: None. K. Tong: None. A. Wang-Selfridge: None. B. Wright: None.